STRATEGI PENGEMBANGAN BISNIS INDUSTRI JASA BIMBINGAN BELAJAR DENGAN METODE ANALISIS SWOT - Nurhayati, Ai (Teknik Industri Fakultas Teknik UNIGAL, 2024)
Education is the foundation of knowledge for growth and development as a provision for living life. The increasing competition among students for achievement means that students need additional learning through additional tutoring institutions. The growth of additional tutoring institutions is increasingly rapid, making competitiveness even higher. The problem that is often faced in the field is that players in the tutoring services industry must try to stay afloat in the midst of the growing competition in the domestic tutoring business. One of the efforts of tutoring institutions to be successful and successful is by developing a tutoring business. The problem formulation in this research is how to develop a tutoring business. The aim of this research is to develop a tutoring business using the SWOT (Strength, Weakness, Opportunities, and Threat) analysis method. The results obtained from this research are the appropriate strategy design, namely the implementation of the SO strategy. The conclusion of this research is that SO (Strength Opportunities) strategies that can be implemented are improving the approach to parents of students, commensurate service fees with services, improving fast response services to students' sudden needs, increasing the professionalism of teachers, improving learning program services both online and offline, improving quality books that are easy for students to understand, allocating teachers according to students' needs and improving facilities.